Exploring women's responses to online media coverage of weight loss surgery. Issue 5 (17th August 2015) - Champion, C.; Glenn, N.; Berry, T.; Spence, J. C.
Summary: The purpose of this study was to understand the reactions of women to online news articles about weight loss surgery and related reader comments. Focus groups were conducted; open‐ended questions were asked to elicit responses to existing online news media content related to weight loss surgery. The participants described the online articles as predominantly supportive of weight loss surgery and in response they expressed a desire to see more critical content, including different and competing perspectives. Participants felt the online comments represented extreme perspectives and were predominately negative. These were therefore not viewed as helpful or informative. Nevertheless, readers viewed comments as a form of entertainment. Because of the aggressive and anonymous nature of reader comments in response to online news stories, the participants did not feel comfortable leaving comments themselves on the news sites. Findings highlight the importance of gathering readers' perspectives in response to interactive media content and, in particular, health information.